Impact of diabetes on platelet activation in different manifestations of atherosclerosis (Swiss Medical Weekly, 2013)
BACKGROUND: Atherosclerosis affects many patients with type 2 diabetes. Both are associated with platelet activation, but it remains unclear how diabetes contributes to, or even enhances, platelet activation in patients with atherosclerosis. We therefore investigated the impact of diabetes on platelet activation and protease activated receptor-1 (PAR-1) mediated platelet response in patients with symptomatic coronary artery disease (CAD), as compared with other manifestations of atherosclerosis. METHODS: Baseline P-selectin expression, thrombin receptor activating peptide-6 (TRAP-6) inducible P-selectin, and relative increase of platelet P-selectin after activation with TRAP-6 were measured using flow cytometry in platelets from 317 patients after angioplasty and stenting for symptomatic atherosclerotic disease, and from 50 healthy controls. RESULTS: Patients with symptomatic atherosclerosis exhibited significantly higher levels of baseline P-selectin expression, TRAP-6-inducible P-selectin and relative increase of platelet P-selectin after stimulation with TRAP-6 than healthy controls. Patients with symptomatic peripheral artery disease or cerebrovascular disease (PAD/CVD) had higher levels of platelet activation and PAR-1-mediated platelet reactivity than patients with symptomatic CAD. Of interest, CAD patients with diabetes responded more strongly to TRAP-6 than those without diabetes, and their platelet activation and PAR-1-mediated platelet reactivity resembled those from PAD/CVD patients. CONCLUSION: Compared with healthy controls, platelets from patients with symptomatic atherosclerotic disease are activated and susceptible to PAR-1-mediated activation. Diabetes affects platelet reactivity only in patients with symptomatic CAD, while other manifestations of atherosclerosis may have an overwhelming effect on platelet reactivity that is not further enhanced by diabetes.